2009
DOI: 10.1155/2009/567120
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Ghrelin and Ghrelin Receptor Genes and Effects on Fat Deposition in Chicken and Duck

Abstract: Ghrelin (GHRL) and its receptor (GHSR) are involved in various bioactivities. In this study, the complete cDNA and 5′ flanking region of the duck GHRL (dGHRL) gene and a 3717 bp fragment of the duck GHSR (dGHSR) gene were obtained. A total of 19, 8, 43, and 48 SNPs identified in 2751, 1358, 3671, and 3567 bp of the chicken GHRL (cGHRL), chicken GHSR (cGHSR), dGHRL, and dGHSR genes, respectively. Both cGHRL and dGHRL were expressed predominantly in the proventriculus, whereas the highest mRNA levels of cGHSR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
1
22
0
2
Order By: Relevance
“…The authors observed tendency that genotype AG had better performance in body height and body length than genotype GG, although no significant differences were observed. In chickens and ducks, the several polymorphisms were found in GHRL gene and some of them were scientifically associated with abdominal fat weight, crude protein content of leg muscle and subcutaneous fat thickness (Nie et al, 2009). Sherman et al (2008) identified in cattle GHRL gene, polymorphism in the third intron but it showed minor associations with the feed efficiency traits.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed tendency that genotype AG had better performance in body height and body length than genotype GG, although no significant differences were observed. In chickens and ducks, the several polymorphisms were found in GHRL gene and some of them were scientifically associated with abdominal fat weight, crude protein content of leg muscle and subcutaneous fat thickness (Nie et al, 2009). Sherman et al (2008) identified in cattle GHRL gene, polymorphism in the third intron but it showed minor associations with the feed efficiency traits.…”
Section: Discussionmentioning
confidence: 99%
“…In layer chicks and Japanese quail, plasma ghrelin levels were elevated after fasting, and the elevation of plasma ghrelin was reversed by refeeding (Shousha et al, 2005a;Kaiya et al, 2007). Avian ghrelin receptors have been identified in chickens (Tanaka et al, 2003), Japanese quail (Kitazawa et al, 2009), and ducks (Nie et al, 2009) and are widely distributed in the brain (Geelissen et al, 2003;Tanaka et al, 2003;Nie et al, 2009) and peripheral tissues (Geelissen et al, 2003;Tanaka et al, 2003;Kitazawa et al, 2009;Nie et al, 2009). Shousha et al (2005a) reported that IP administration of low doses (0.5 -1 nmol/bird) of ghrelin stimulated food intake in Japanese quail, although the highest dose (3 nmol/bird) of ghrelin suppressed food intake.…”
Section: Ghrelinmentioning
confidence: 99%
“…The brain is the tissue showing the second highest expression of the ghrelin receptor in fish and birds. In addition, the ghrelin receptor gene expression has also been detected in various amounts in more or less all peripheral tissues, such as the eyes, heart, thymus, liver, stomach, intestine, spleen, gill, gall bladder, muscle, kidney, head kidney, Brockmann bodies, skin, muscle, and gonads for fish , Chen et al 2008, Kaiya et al 2009a,b, Small et al 2009, Cruz et al 2010, the stomach and gonads, and to a lesser extent in the small and large intestines, adrenal gland, and kidney in frogs (Kaiya et al 2011a), and the heart, lung, thymus, liver, spleen, pancreas, gastrointestinal tract, adrenal gland, kidney, gonads, breast muscle, subcutaneous fat, leg muscle, abdominal fat, and uropygial gland in birds (Geelissen et al 2003, Tanaka et al 2003, Saito et al 2005, Richards et al 2006, Kitazawa et al 2009, Nie et al 2009). In birds, strain differences (Geelissen et al 2003, Tanaka et al 2003, Richards & McMurtry 2010) and a regionspecific expression in the gastrointestinal tract (Kitazawa et al 2009) have been reported.…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 99%
“…Similar to mammals, the GHS-R1a or GHS-R1a-LR transcripts have been found in various brain regions and peripheral organs, and the pituitary is the predominant expressing site for the ghrelin receptor isoforms in the majority of species, e.g. the channel catfish (Small et al 2009), chickens (Geelissen et al 2003, Tanaka et al 2003, Saito et al 2005, Richards et al 2006, Yamamoto et al 2008, and ducks (Nie et al 2009) for GHS-R1a, and in the black porgy , orange-spotted grouper (Chen et al 2008), and rainbow trout (Kaiya et al 2009b) for GHS-R1a-LR. An exception is frogs, where GHS-R1a mRNA is not detected in the pituitary but mainly in the brain (Kaiya et al 2011a).…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 99%